Migration from Gasoline to Gaseous Fuel for Small-scale Electricity Generation Systems - Seno D. Panjaitan; Yandri Yandri; Sukandar Sukandar; Berlian Sitorus (Universitas Ahmad Dahlan, 2013)
This paper describes a study that gives a consideration to change fuel source for electriccity generator from gasoline to combustible gas. A gaseous fuel conversion technology is presented and its performance is compared with gasoline. In the experiment, two types of load were tested, resistive and resistive-inductive. By using both fuels mostly the power factor (Cos φ) of resistive-inductive load variations were greater than 0.8, and they had slight difference on operational voltage. The drawback of using gaseous fuel is the frequency of the electricity might be not reach the standard frequency (i.e. 50 Hz). In the lab scale experiment, the gasoline consumption increased proportionally with the load increase, while using gaseous fuel the consumption of gas equal also increased where the average consumption value is 100 gram per 15 minutes operation for the tested load in the experiment. The main advantage using gaseous fuel (liquefied petroleum gas or biogas) compared to gasoline is a cleaner emitted gas after combustion.